2022
DOI: 10.3390/healthcare10101935
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Work Systems, Thriving at Work, and Job Burnout among Nurses in Chinese Public Hospitals: The Role of Resilience at Work

Abstract: The overall purpose of this study is to explore and examine whether high-performance work systems (HPWS) can impact thriving at work and job burnout via resilience at work among nurses in Chinese public hospitals. Specifically, it draws on social exchange theory to conceptualize a positive relationship between HPWS and resilience at work. Then, based on a socially embedded model of thriving at work and knowledge about job burnout in the literature, it further proposes the differentiated mediation roles of resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…It was demonstrated that OIs were associated with HCWs’ TW. The findings were consistent with prior research dedicated to employees’ perceptions of perceived organizational support and service employees’ TW (Alothmany et al., 2022; Yun et al., 2022).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was demonstrated that OIs were associated with HCWs’ TW. The findings were consistent with prior research dedicated to employees’ perceptions of perceived organizational support and service employees’ TW (Alothmany et al., 2022; Yun et al., 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Such OIs are aimed at enhancing employees’ work outcomes and, consequently, organizational performance (Shin et al., 2012). OIs may enhance HCWs’ TW, as employees’ perceptions of perceived organizational support and experienced service‐oriented high‐performance work systems have been proved to enhance service employees’ TW (Yun et al., 2022) and consequently their health and performance (Jo et al., 2020; Zhu et al., 2021).…”
Section: Antecedents References Industrymentioning
confidence: 99%
“…Management approaches targeting workplace resilience, such as implementing high-performance work systems, improving organizational practices, strengthening team cohesion, and providing cognitive-behavioral coaching, may help address the work-related challenges these nurses face. 16,36,37 However, the existing literature on this topic is somewhat fragmented, pointing to the value of adopting a more comprehensive theoretical framework, such as the self-determination theory, which highlights the fundamental human needs for relatedness, competence, and autonomy. 38 A study has also revealed that work engagement and communication skills act as mediators in the relationship between work-family conflict and nurses' ability to maintain job satisfaction, within the context of the job-demand-requirement (JD-R) model, 19 providing a work environment that meets individual needs for autonomy, competence and relatedness can improve intrinsic motivation, 39 balancing individual-organizational mismatch, organizational factors (eg, workload, control, reward, community, fairness, organizational values).…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested that the development of resilience can lead to increased thriving and decreased work alienation. 16 In Chinese nurses, work-family conflict has been found to be linked to alienation, with psychological capital acting as a mediator in this relationship. [16][17][18] Psychological capital represents an advantageous asset in mitigating nurses' sense of alienation.…”
Section: The Effect Of Psychological Resiliencementioning
confidence: 99%
See 1 more Smart Citation